Hesperidin plays beneficial roles in disorders associated with the central nervous system: a review - Ayomide Victor Atoki; Patrick Maduabuchi Aja; Tijjani Salihu Shinkafi; Erick Nyakundi Ondari; Chinaza Godswill Awuchi (International Journal of Food Properties)
Significant levels of flavonoids with antioxidant properties can be found in citrus species. Flavonoids are a class of plant chemical known for a wide range of pharmacological activities. Notable among these flavonoids is Hesperidin. It has quite a number of biological properties, like anti-inflammatory and antioxidant properties. Numerous studies have examined the biological impacts of hesperidin and its underlying mechanisms throughout the last few decades. Hesperidin’s antioxidant properties have led to a thorough evaluation of this phytochemical’s cardioprotective and anti-cancer properties. To assess the underlying neuropharmacological processes of hesperidin, numerous cellular and animal models have been created. Additionally, its neuroprotective activity has been validated by clinical data. Hesperidin reduces neuroinflammatory and apoptotic pathways to exert its neuroprotective effects. In preclinical models for disorders of the central nervous system, hesperidin function has been investigated. Hesperidin has been shown to enhance memory and cognition while successfully treating depression. Although the biological activities of hesperidin in neurodegenerative diseases have been evaluated, more investigation into its underlying mechanisms is required to understand its function in a number of central nervous system disorders, including autoimmune demyelinating disease and neurodegenerative diseases. Thus, this study focuses on the potential role of hesperidin in several models of central nervous system neuroinflammation, such as experimental autoimmune encephalomyelitis, and on the potential role of hesperidin in various neurodegenerative diseases, with a focus on its antioxidant, anti-apoptotic, and anti-inflammatory properties. Information about the usage of hesperidin as a nutraceutical to prevent certain CNS illnesses based on recent research is provided.